2017
DOI: 10.15287/afr.2017.805
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratios and reforestation potential in Acacia koa populations on Hawai’i

Abstract: Lawson S. S., Pike C. C. 2017. Stable isotope ratios and reforestation potential in Acacia koa populations on Hawai'i. Ann. For. Res. 60(2): 279-295.Abstract. Stable carbon and nitrogen isotopes can be influenced by a multitude of factors including elevation, precipitation rate, season, and temperature. This work examined variability in foliar stable carbon (δ13C) and nitrogen (δ15N) isotope ratios of koa (Acacia koa) across 17 sites on Hawai'i Island, delineated by elevation and precipitation gradients. Sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Water use efficiency by plants has been reported to decrease with water in the soil and increase with the soil water decline (Fang et al 2010;Hartman and Danin 2010;Lawson and Pike 2017;Mapope and Dakora 2016). In this present study, the values obtained show these accessions could be stable in their expression of water use.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Water use efficiency by plants has been reported to decrease with water in the soil and increase with the soil water decline (Fang et al 2010;Hartman and Danin 2010;Lawson and Pike 2017;Mapope and Dakora 2016). In this present study, the values obtained show these accessions could be stable in their expression of water use.…”
Section: Discussionsupporting
confidence: 56%
“…The δ 15 N value varied from 3.34 (Tpt18) to 0.86 (Tpt3-B) in the shoots and from 3.07 (Tpt15) to 0.49 (Tpt32) for roots (Table 8). The δ 13 C of C3 plants explained their water-use ability (Lawson and Pike 2017). Analysis of variance of δ 13 C from shoots and roots revealed highly significant variation (p= ≤.0001.)…”
Section: Resultsmentioning
confidence: 95%
“…Neirynck et al [ 48 ] mentioned that different tree species such as Acer psedoplatanus , Fraxinus excelsior , and Tilia platyphyllos significantly affect the C:N ratio and it was related mainly to litter quality. Lovett et al [ 49 ] also revealed that forest structure alters the C and N dynamics because species composition affects nutrient cycling under their different canopy structures, which can substantially influence the forest ecosystems’ overall nutrient turnover rates [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rehman et al [ 53 ] reported that various forest protection activities could influence stable isotopic abundance and C:N ratios. Moreover, it is generally believed that multiple factors such as light availability, litter input, water use efficiency, soil physical, chemical, and biological properties altered by the forest types may affect natural isotopic abundance in forest ecosystems [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%